2022
DOI: 10.1016/j.envres.2021.112072
|View full text |Cite
|
Sign up to set email alerts
|

Transition from saliva droplets to solid aerosols in the context of COVID-19 spreading

Abstract: To control the evolution of a pandemic such as COVID-19, knowing the conditions under which the pathogen is being transmitted represents a critical issue, especially when implementing protection strategies like social distancing and face masks wearing. For viruses and bacteria that spread via airborne and/or droplet pathways, this requires understanding how saliva droplets evolve over time after their expulsion by speaking or coughing. Within this context, the transition from saliva droplets to solid residues,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 41 publications
(58 reference statements)
0
36
0
Order By: Relevance
“…For a droplet of pure water, we may assume the vapor pressure at the droplet surface p v,p is the vapor pressure corresponding to the droplet temperature p v,p = p sat (T p ), as we considered the air film around the droplet to be fully-saturated. Accurate modeling of the evaporation of saliva can be rather complex, and thus most studies simplify the saliva as an ideal solution of dissolved inorganic salts [9,47,58]. This simplification allows for the estimation of the vapor pressure using Raoult's law,…”
Section: Mass Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…For a droplet of pure water, we may assume the vapor pressure at the droplet surface p v,p is the vapor pressure corresponding to the droplet temperature p v,p = p sat (T p ), as we considered the air film around the droplet to be fully-saturated. Accurate modeling of the evaporation of saliva can be rather complex, and thus most studies simplify the saliva as an ideal solution of dissolved inorganic salts [9,47,58]. This simplification allows for the estimation of the vapor pressure using Raoult's law,…”
Section: Mass Equationmentioning
confidence: 99%
“…As the droplet's water content evaporates, it may transition from a saliva droplet to a solid residue, featuring a unique behavior; regardless of its initial diameter and the ambient conditions, the final diameter is set to be roughly 20% of the initial droplet diameter [47,48]. This aerosol might remain stable for hours and would nearly suspend in the ambient air due to its small mass [49].…”
Section: Introductionmentioning
confidence: 99%
“…The outbreak of SARS, MERS, and the Novel Coronavirus SARS-CoV-2 illustrates that virus transmission and infection are very complex problems. Droplet aerosol is one of the crucial ways for most microorganisms (including viruses, bacteria and fungi) to spread in the air [1][2][3][4]. People usually release droplet aerosols by coughing or breathing, and then the droplet aerosols spread through the air until they are inhaled into the body or deposited on surfaces [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is marked by various characteristics that occur in the environment, such as, for example, relative humidity (RH) and ambient temperature among others, Ugarte-Anero et al [1], Wang et al [10] and Sen et al [11]. Stiti et al [12] shows that a droplet of an initial diameter of 21 µm in 2 seconds could become an aerosol when a temperature above 20ºC and an RH below 80% occurs. Studies such as Xie et al [13], Liu et al [14] and Ugarte-Anero et al [1] state that at higher relative humidity the evaporation time of these is longer.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon depends on many factors; the speed at which it is generated, whether we are in a closed or open place, anyhow there is a high-speed wind or a soft breeze, regardless there is ventilation, etc. Stiti [12] has found that a particular 80 µm becomes solid waste before reaching the ground when the person exhaling it has a height of 1.6 meters from the mouth to the ground. CFD studies such as Dbouk et al [15] and Li et al[16] warn that with an external wind greater than 1.1 m/s can reach up to 6 meters away.…”
Section: Introductionmentioning
confidence: 99%